Solar cell and preparation method thereof

By using copper electrode slurry and laser processes in silicon heterojunction solar cells, and forming periodic nanostructure arrays on transparent conductive films, the complex and cost-effective electrode preparation in the prior art is solved, and the problem of achieving the realization of the problem of High-efficiency and low-cost solar cell production.

CN119451296APending Publication Date: 2025-02-14GUANGDONG UNIV OF TECH +1

Patent Information

Application Number
CN202310949865.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-28
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

In the electrode preparation process, existing silicon heterojunction solar cells have problems such as complex process, high cost and limited conversion efficiency, especially low-temperature silver paste has poor conductivity and high manufacturing costs.

Method used

Metal electrodes are prepared using copper electrode slurry and laser processes, and periodic nanostructure arrays are formed on transparent conductive films to improve conductivity and light absorption while simplifying the process flow.

Benefits of technology

It realizes efficient and low-cost copper electrode preparation, improves the conversion efficiency and durability of solar cells, and reduces manufacturing costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119451296A_ABST
    Figure CN119451296A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of photovoltaic cells, and provides a solar cell and a preparation method thereof, the solar cell comprises a silicon substrate and a transparent conductive film, the transparent conductive film is provided with a periodic nanostructure array, and the solar cell also comprises a metal electrode arranged on the surface of the transparent conductive film, the metal electrode is prepared by adopting copper electrode slurry and a laser process. The periodic nanostructure array modified layer is prepared on the conductive thin film, so that the surface area and the conductivity of the transparent conductive thin film can be increased, the absorption and reflection of the transparent conductive thin film to light are improved, and the efficiency of the solar cell is improved; and the binding force of the electrode can be increased, and the durability and the stability of the solar cell are improved. According to the preparation method of the solar cell provided by the invention, the position of the copper electrode can be precisely processed, the problem of precision of current silk-screen printing is solved, the damage to the amorphous silicon layer can be avoided, the prepared copper electrode has a relatively large height-width ratio, and the light conversion efficiency can be effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of photovoltaic cells, and in particular to a solar cell and a preparation method thereof. Background Art

[0002] Silicon heterojunction (HJT) cells are a type of high-efficiency solar cell. They have become one of the most promising solar cell technologies due to their advantages such as simple process, high conversion efficiency, low-temperature process, and double-sided power generation. The metal grid electrode is the most important structure and material in silicon heterojunction cells. Its main function is to collect carriers generated by the photovoltaic effect, thereby drawing out the current generated by the photovoltaic effect.

[0003] At present, the most commonly used method for preparing electrodes in the industry is screen printing silver paste, which has the advantages of simple and mature process and suitable for mass production. However, due to the precision of the printing plate, the electrode aspect ratio is small, the shading area is large, the screen printing process is becoming more and more difficult, and the yield rate caused by virtual printing and broken grids has dropped significantly, which limits the further improvement of the conversion efficiency of solar cells. On the other hand, due to the inherent characteristics of HJT cells, the processing technology needs to be controlled at around 200°C, and low-temperature silver paste needs to be used. However, low-temperature silver paste has poor conductivity, high contact resistance with ITO film (Transparent Conductive Oxide), poor printing performance, and a large weight gain of the paste of the heterojunction battery, accounting for about 30-40% of the cost of the entire heterojunction processing battery. In addition, the price of silver paste is expensive, which makes the manufacturing cost of solar cells high, which is not conducive to the development of batteries in the direction of high efficiency and low cost.

[0004] In order to reduce costs and increase efficiency, more and more solar cell manufacturers have turned to the development of copper electrodes with high conductivity and low cost. The most commonly used method at present is electroplating. The preparation of copper grid electrode by electroplating is to first deposit a layer of seed copper on the surface of ITO, then pattern the mask, and then electroplate copper and tin. However, this method needs to consider the subsequent etching and removal of the mask and seed layer. The process is relatively cumbersome, and the bonding strength between the copper electrode and the substrate has always been a problem in the industry. In addition, since there is no mature electroplating equipment developed specifically for heterojunction batteries on the market, the equipment is basically transformed from the traditional PCB (printed circuit board) industry, so the operating cost and processing quality cannot fully meet the expected requirements, which runs counter to the goal of reducing costs and increasing efficiency.

[0005] Therefore, it is of great significance to develop a method for preparing copper electrodes for silicon heterojunction solar cells with simple process and low cost. Summary of the invention

[0006] The purpose of the present invention is to overcome the above-mentioned problems existing in the prior art, and to provide a solar cell, which includes a silicon substrate and a transparent conductive film, on which a periodic nanostructure array is arranged, and also includes a metal electrode arranged on the surface of the transparent conductive film, and the metal electrode is prepared by using a copper electrode slurry and a laser process. Preparing a periodic nanostructure array modified layer on the conductive film can increase the surface area and conductivity of the transparent conductive film, improve the absorption and reflection of light by the transparent conductive film, and improve the efficiency of the solar cell; it can also increase the bonding force of the electrode, and improve the durability and stability of the solar cell.

[0007] In order to achieve the above objective, the present invention provides a solar cell in a first aspect, which comprises a silicon substrate and a transparent conductive film, wherein a periodic nanostructure array is arranged on the transparent conductive film.

[0008] In one example, the solar cell also includes a metal electrode arranged on the surface of the transparent conductive film, and the metal electrode is prepared by copper electrode slurry and laser process; wherein the copper electrode slurry includes a metal composition, a dispersing reducing agent, a composite curing agent and optionally a solvent; the metal composition includes at least copper powder, and optionally gold powder and / or silver powder; the composite curing agent includes a thermosetting resin and a latent curing agent.

[0009] The second aspect of the present invention provides a method for preparing the solar cell described in the first aspect of the present invention, which comprises using ultrafast laser to process a transparent conductive film.

[0010] In one example, the method comprises the following steps:

[0011] (1) Using ultrafast laser to process the surface of transparent conductive film;

[0012] (2) placing a copper electrode slurry on the surface of the transparent conductive film treated in step (1);

[0013] (3) Performing a first laser scan on the copper electrode slurry coating on the surface of the transparent conductive film in step (2).

[0014] The present invention adopts the above technical solution to achieve the following beneficial effects:

[0015] (1) The solar cell provided by the present invention can increase the surface area of ​​the transparent conductive film, enhance the surface plasmon resonance effect, promote the generation and transfer of charge carriers in the film, and increase its conductivity by preparing a periodic nanostructure array modified layer on the conductive film; it can also change the optical properties of the transparent conductive film, improve the absorption and reflection of light by the transparent conductive film, and improve the absorption efficiency of the solar cell; it can also increase the bonding force of the electrode, thereby improving the durability and stability of the solar cell.

[0016] (2) In the solar cell provided by the present invention, the copper electrode slurry used uses a metal composition containing copper powder as a precursor material to prepare a coating to prepare a copper electrode, which replaces the use of expensive silver paste, greatly reduces the production cost of solar cell electrodes, and can well meet the needs of high efficiency and low cost in industrial production.

[0017] (3) The method for preparing solar cells provided by the present invention can accurately process the position of the copper electrode due to the high controllability of laser processing, thus solving the current problem of screen printing accuracy and avoiding damage to the amorphous silicon layer. The prepared copper electrode has a large aspect ratio, which can effectively improve the light conversion efficiency.

[0018] (4) Compared with the traditional seed layer plating method, the solar cell preparation method provided by the present invention does not require a mask, avoids the processes such as mask patterning and seed layer removal, simplifies the process and reduces the cost; and the processed pattern can be directly and flexibly changed through drawing software such as CAD, so that complex copper electrode circuit morphology can be processed more flexibly.

[0019] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 Shown is a schematic structural diagram of a heterojunction battery in an example.

[0021] Figure 2 The figure shows a process flow chart for preparing copper electrodes for heterojunction batteries in one example.

[0022] Figure 3 The figure shows a schematic diagram of the process for preparing a copper electrode for a heterojunction battery in one example.

[0023] Figure 4 The figure shows a schematic structural diagram of a laser processing system in one example.

[0024] Figure 5 FIG. 1 is a schematic diagram of a laser processing operation in one example.

[0025] Figure 6 Shown are top-view schematic diagrams of periodic nanostructure arrays, wherein a is a top-view schematic diagram of the periodic nanostructure obtained in Example 1, b is a top-view schematic diagram of the periodic nanostructure obtained in Example 2, and c is a top-view schematic diagram of the periodic nanostructure obtained in Example 3.

[0026] Figure 7 Shown are three-dimensional schematic diagrams of periodic nanostructure arrays, wherein a is a three-dimensional schematic diagram of the periodic nanostructure obtained in Example 1, b is a three-dimensional schematic diagram of the periodic nanostructure obtained in Example 2, and c is a three-dimensional schematic diagram of the periodic nanostructure obtained in Example 3.

[0027] Figure 8 Shown is a schematic diagram of the three-dimensional morphology of the copper electrode of a heterojunction battery in one example.

[0028] Fig. 9 The figure shows a schematic diagram of the overall circuit of the copper grid line of a heterojunction solar cell in an example.

[0029] Figure numerals: 1-metal electrode; 2-transparent conductive film; 3-p-type amorphous silicon film; 4-n-type amorphous silicon film; 5-intrinsic amorphous silicon film; 6-copper electrode slurry coating; 7-laser; 8-heterojunction battery substrate; 9-periodic nanostructure array; 10-laser; 11-attenuation plate; 12-aperture; 13-wave plate; 14-beam expander; 15-reflector; 16-CCD image sensor; 17-galvanometer; 18-field mirror; 19-moving platform. DETAILED DESCRIPTION

[0030] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.

[0031] Unless otherwise defined, all scientific and technical terms used in the present invention have the same meanings as commonly understood by one of ordinary skill in the art to which the present invention relates.

[0032] A first aspect of the present invention provides a solar cell, which includes a silicon substrate and a transparent conductive film, wherein a periodic nanostructure array is arranged on the transparent conductive film.

[0033] The specific morphology of the periodic nanostructure array is not limited. For example, the periodic nanostructure array can be a transverse stripe distribution array, a longitudinal stripe distribution array, an oblique stripe distribution array, a radial stripe distribution array, a concentric ring distribution array, a ripple distribution array, a diamond distribution array, or any other regular or irregular pattern distribution array.

[0034] In one example, the transparent conductive film is processed by ultrafast laser to obtain a periodic nanostructure array, and the conditions of the ultrafast laser processing include laser polarization.

[0035] There is no limitation on the laser polarization mode, and it can be freely adjusted according to the pattern of the preset periodic nanostructure array. In one example, the laser polarization includes linear polarization and / or circular polarization.

[0036] Linearly polarized laser refers to laser whose electric field vector vibrates along a straight line in space. The electric field vector of linearly polarized laser can vibrate in any direction. In some cases, linear polarization can be divided into horizontal polarization and vertical polarization. In some cases, linear polarization also includes radial polarization and azimuthal polarization, which are special linear polarizations. The electric field vector of radial polarization vibrates in the radial direction, which means that the vibration direction of the electric field vector radiates radially from the center of the laser beam. The electric field vector of azimuthal polarization vibrates in the azimuthal direction, which means that the vibration direction of the electric field vector rotates around the axis of the laser beam.

[0037] Circularly polarized laser refers to laser whose electric field vector moves in a circle in space. Circularly polarized laser can be divided into left-handed circular polarization and right-handed circular polarization. In left-handed circular polarization laser, the electric field vector rotates counterclockwise; in right-handed circular polarization laser, the electric field vector rotates clockwise.

[0038] The inventors of the present invention have found that by using ultrafast laser to process transparent conductive films, periodic nanostructure arrays of various complex shapes can be prepared by changing laser processing parameters such as laser polarization and energy flux density. When the ultrafast laser acts on the transparent conductive film, the transparent conductive film is excited to form a surface plasma layer. The plasmons interfere with the laser and cause a periodic distribution of energy, forming a temperature gradient. Electrons transfer energy to the lattice through acoustic-electric coupling, causing ablation of the material and eventually forming a periodic nanostructure array. The nanostructure on the surface of the transparent conductive film can improve the solar energy absorption rate. Therefore, the solar energy absorption rate can be further increased by adjusting the periodic nanostructure array.

[0039] The processing parameters of the ultrafast laser can be freely adjusted according to the pattern of the preset periodic nanostructure array.

[0040] In one example, the processing parameters of the ultrafast laser include: laser wavelength of 300nm-1060nm, laser pulse width of 100fs-20ps, laser energy flux density of 0.1J / cm 2 -10J / cm 2 , frequency is 1KHz-1MHz, laser scanning speed is 0.1mm / s~100mm / s, and defocus is +0mm~+2mm.

[0041] The inventors of the present invention have found that by preparing a periodic nanostructure, the light absorption rate and conductivity of the transparent conductive film can be increased, and at the same time, the bonding force between the metal electrode and the transparent conductive film can be increased, which is conducive to the durability and stability of the solar cell.

[0042] In one example, the solar cell further includes a metal electrode disposed on the surface of the transparent conductive film, and the metal electrode is prepared by using copper electrode slurry and laser process.

[0043] In one example, the copper electrode slurry includes a metal composition, a dispersed reducing agent and a composite curing agent; the metal composition includes at least copper powder, and optionally gold powder and / or silver powder; the composite curing agent includes a thermosetting resin and a latent curing agent; wherein the mass ratio of the metal composition to the composite curing agent is (7-30):1.

[0044] It should be noted that, in addition to copper powder, the metal composition may also contain gold powder and / or silver powder, as well as other metal powders with good electrical conductivity. The metal composition may be a combination of one or more of various forms of the above-mentioned metal elements, such as simple substances, oxides, hydroxides or salts, which is not limited and can be selected according to actual needs. For example, the metal composition may be a combination of three metal simple substances of copper, gold and silver, or may be a combination of three metal oxides.

[0045] In one example, the metal composition is in powder form, and the particle size is nanometer scale.

[0046] In one example, the metal composition includes nano copper oxide and / or nano cuprous oxide.

[0047] In one example, the metal composition is nano copper oxide, or may be nano cuprous oxide.

[0048] In one example, the metal composition is a composition of nano-copper oxide and nano-cuprous oxide. The ratio of the two is not limited and can be adjusted according to the actual sequence. Exemplarily, the mass ratio of nano-copper oxide to nano-cuprous oxide can be (1-5):1.

[0049] The copper electrode slurry of the present invention has the advantages of good dispersibility and high reduction rate, and the composite curing agent prepared by using a thermosetting resin and a latent curing agent can make the bonding force of the electrode prepared by the copper electrode slurry higher.

[0050] In one example, the mass ratio of the metal composition to the composite curing agent is (7-30):1, for example, it can be 7:1, 10:1, 12:1, 15:1, 16.4:1, 18:1, 20:1, 25:1, 28:1, or 30:1.

[0051] In a preferred embodiment, the mass ratio of the metal composition to the composite curing agent is (15-20):1.

[0052] In order to further improve the performance of the copper electrode slurry and prepare a metal electrode with better physical properties, one or more of the characteristics may be optimized.

[0053] In one example, the thermosetting resin is at least one selected from epoxy resin, polyurethane-modified epoxy resin, acrylic-modified epoxy resin, polyamide resin, polyurethane resin and acrylic resin.

[0054] In one example, the thermosetting resin is epoxy resin.

[0055] In one example, the latent curing agent includes a latent amine curing agent and / or an imidazole curing agent. The latent curing agent can be a latent amine curing agent alone, an imidazole curing agent, or a combination of a latent amine curing agent and an imidazole curing agent.

[0056] Exemplarily, the latent amine curing agent is a dicyandiamide curing agent, which exemplarily includes MY-24, MY-25 and MY-HK-1.

[0057] Exemplarily, the imidazole curing agent includes PN-23J, PN-50, PN-23, PN-31 and PN-40.

[0058] In one example, the latent curing agent is a latent amine curing agent and an imidazole curing agent. The mass ratio of the latent amine curing agent and the imidazole curing agent is not limited and can be freely adjusted according to actual needs.

[0059] Exemplarily, the mass ratio of the thermosetting resin to the latent curing agent may be (4-6):1, for example, 4:1, 5:1, or 6:1.

[0060] The combination of latent amine curing agent and imidazole curing agent, and thermosetting resin, especially epoxy resin therein, to form a composite curing agent can make the copper electrode slurry cure faster and improve the bonding strength between the copper electrode slurry and the contact surface.

[0061] In one embodiment, the reducing dispersant is selected from at least one of polyvinyl pyrrolidone and its derivatives. The specific type of the derivative is not limited, for example, it can be a copolymer of polyvinyl pyrrolidone, or a reactant of polyvinyl pyrrolidone and other compounds, as long as the derivative can play a similar or better dispersing and reducing role as polyvinyl pyrrolidone.

[0062] In one example, the mass ratio of the metal composition to the dispersing reducing agent is (2-9):1, for example, 2:1, 2.5:1, 3:1, 3.5:1, 4:1, 4.5:1, 5:1, 5.5:1, 6:1, 6.5:1, 7:1, 7.5:1, 8:1, 8.5:1, 8.74:1, 9:1.

[0063] In a preferred embodiment, the mass ratio of the metal composition to the dispersing reducing agent is (2.5-6):1.

[0064] The present invention selects polyvinyl pyrrolidone and its derivatives which have both dispersing and reducing effects as dispersing reducing agents, and limits the mass ratio of the metal composition and polyvinyl pyrrolidone and its derivatives, so that the copper electrode slurry has the advantages of good dispersibility and high reduction rate, improves the process efficiency of subsequent copper electrode preparation, and makes it easier to obtain copper electrodes with uniform thickness.

[0065] The type of solvent is not specifically limited, as long as it can dissolve the metal composition, disperse the reducing agent, and the composite curing agent, and does not react with the solute components. In one example, the solvent can be selected from C1-C6 low-carbon alcohols, or other types of organic solvents can be selected in the art.

[0066] In one example, the low-carbon alcohol includes at least one of ethylene glycol, polyethylene glycol, pentanol, propanol, butanol and isobutanol.

[0067] In one example, the mass ratio of the metal composition to the solvent is (0.3-2):1, for example, 0.3:1, 0.34:1, 0.5:1, 0.8:1, 1:1, 1.2:1, 1.5:1, 1.86:1, or 2:1.

[0068] In a preferred embodiment, the mass ratio of the metal composition to the solvent is (1-1.6):1.

[0069] In one example, the mass ratio of the solvent to the dispersing reducing agent is (1.8-14):1, for example, it can be 1.8:1, 2:1, 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1, 10:1, 11:1, 12:1, 13:1, 13.6:1, 14:1.

[0070] In a preferred embodiment, the mass ratio of the solvent to the dispersing reducing agent is (2-5):1.

[0071] By limiting and optimizing the mass ratio of the metal composition and the solvent, as well as the mass ratio of the dispersing reducing agent and the solvent, the solid content of the copper electrode slurry can be controlled within an appropriate range, so that the copper electrode slurry contains more metal composition while having good dispersibility, which facilitates the coating of the copper electrode slurry and improves the thickness and uniformity of the prepared metal electrode.

[0072] In one example, the copper electrode slurry includes nano copper oxide, polyvinyl pyrrolidone, epoxy resin, latent amine curing agent, imidazole curing agent and ethylene glycol, wherein the proportion of each component is within the above-listed proportion range.

[0073] The present invention also provides a method for preparing a copper electrode slurry, which comprises the following steps:

[0074] (i) mixing the reducing dispersant and the solvent in the formulated amount in batches for multiple times to obtain a mixed solution under the combined action of heating, magnetic stirring and ultrasonic vibration;

[0075] (ii) adding the metal composition and the composite curing agent in the formulated amount to the mixed solution obtained in step (1) in batches for multiple times, and obtaining a copper electrode slurry under the combined action of heating, magnetic stirring and ultrasonic vibration.

[0076] The heating in steps (i) and (ii) can be performed in a water bath at 45-65° C. The number of batches is not limited and can be freely adjusted according to the different formulation contents.

[0077] The process conditions for heating, magnetic stirring and ultrasonic vibration in steps (i) and (ii) are not particularly limited and can be freely adjusted according to the amount and mixing state of the solution.

[0078] The second aspect of the present invention provides a method for preparing the solar cell described in the first aspect of the present invention, comprising using ultrafast laser to process a transparent conductive film.

[0079] In one example, the ultrafast laser processing conditions include laser polarization.

[0080] In one example, the laser polarization includes linear polarization and / or circular polarization.

[0081] In one example, the linear polarization is selected from at least one of horizontal polarization, vertical polarization, radial polarization and azimuthal polarization. In one example, the circular polarization is selected from left-handed circular polarization or right-handed circular polarization.

[0082] In one example, the processing parameters of the ultrafast laser include: laser wavelength of 300nm-1060nm, laser pulse width of 100fs-20ps, laser energy flux density of 0.1J / cm 2 -10J / cm 2, frequency is 1KHz-1MHz, laser scanning speed is 0.1mm / s~100mm / s, and defocus is +0mm~+2mm.

[0083] In one embodiment, the method for preparing the solar cell comprises the following steps:

[0084] (1) Ultrafast laser treatment of the surface of a transparent conductive film to obtain a periodic nanostructure array;

[0085] (2) placing a copper electrode slurry on the surface of the transparent conductive film treated in step (1);

[0086] (3) Performing a first laser scan on the copper electrode slurry of step (2) to obtain a patterned Cu circuit.

[0087] In one example, the schematic diagram of the overall circuit of the patterned Cu circuit is as follows: Fig. 9 shown.

[0088] In one example, in step (2), the thickness of the copper electrode slurry coating can be controlled by selecting the parameters of the coater. For example, the thickness of the copper electrode slurry can be set to 1 um-40 um.

[0089] In one example, in step (2), the copper electrode slurry is disposed on the surface of the transparent conductive film by coating, and dried to obtain a dry copper electrode slurry coating. The drying method is not specifically limited, as long as the purpose of drying can be achieved. For example, a drying oven can be used for drying, the drying temperature can be 50°C-70°C, and the drying time can be 20-40 minutes.

[0090] In one example, the method for preparing a solar cell further includes step (4): performing an Nth laser scan on the copper electrode paste of step (2), where N≧2. Specifically, it can be interpreted as performing an Nth laser scan on the Cu circuit pattern obtained in step (2).

[0091] There is no limitation on the energy of the Nth laser scan, and it can be less than, equal to or greater than the energy of the first laser scan.

[0092] In one example, when the energy of the Nth laser scan is greater than the energy of the first laser scan, the copper electrode can be remelted and solidified by increasing the laser energy, so that the copper electrode and the transparent conductive film are connected with high quality, thereby improving the adhesion of the electrode to the surface of the transparent conductive film.

[0093] In one example, when the energy of the Nth laser scan is less than or equal to the energy of the first laser scan, the laser energy can be accumulated by increasing the value of N and performing multiple scans. The copper electrode can also be remelted and solidified to achieve high-quality connection between the copper electrode and the transparent conductive film, thereby improving the adhesion of the electrode to the surface of the transparent conductive film.

[0094] In one example, the laser energy of the Nth laser scan is higher than the laser energy of the first laser scan. Preferably, the Nth laser scan has a higher energy, and reducing the number of scans can also obtain a preset metal electrode, saving processing procedures.

[0095] The inventors of the present invention have found that since laser selective metal patterning is a photochemical reaction, the required temperature is relatively low, and it is difficult to achieve effective connection between the copper electrode and the transparent conductive film, and the adhesion is poor. Usually, sintering is required to improve the bonding strength between the copper electrode and the silicon substrate. The present invention can achieve remelting and solidification of the copper electrode by increasing the laser energy for a small number of scans, or multiple scans with a low accumulated laser energy, so as to achieve high-quality connection between the copper electrode and the transparent conductive film, thereby improving the adhesion. At the same time, due to the high controllability of the laser, only the copper electrode can be processed, and no sintering is required, thereby avoiding damage to the amorphous silicon layer by the sintering furnace.

[0096] In one embodiment, the method for preparing a solar cell further comprises step (5): rinsing with deionized water to remove the remaining copper electrode slurry coating in the laser unprocessed area to obtain a heterojunction solar cell copper electrode. The cleaning solution is not limited to the deionized water listed above, and other cleaning solutions may also be applicable to the present invention.

[0097] In one embodiment, a method for preparing a solar cell is described by referring to Figure 2 , Figure 3 and Figure 5 As shown, it includes the following steps:

[0098] (a) preparing a heterojunction battery substrate 8, which can be carried out in a conventional manner in the art;

[0099] (b) using ultrafast laser to process the surface of the transparent conductive film 2 to obtain a periodic nanostructure array 9;

[0100] (c) cleaning the surface of the transparent conductive film 2 after being treated in step (b) with a water-based cleaning agent;

[0101] (d) preparing a copper electrode slurry, and placing the slurry on the surface of the transparent conductive film to form a coating 6;

[0102] (e) The first laser 7 scans selective metal patterning to prepare the copper electrode 1;

[0103] (f) Nth laser 7 scan to remelt and solidify the copper electrode;

[0104] (g) Removing the remaining copper electrode slurry coating in the laser unprocessed area to obtain the heterojunction solar cell copper electrode.

[0105] In one example, in step (e), the laser parameters used in the first laser scan include: laser pulse energy of 1nJ to 500nJ, laser scanning speed of 1mm / s to 500mm / s, defocus of +0mm to +2mm, laser pulse width of 100fs-20ps, frequency of 1KHz-70MHz, and laser wavelength of 300-1100nm.

[0106] In one example, in step (f), the laser parameters used in the Nth laser scan include: laser pulse energy of 25nJ to 500nJ, laser scanning speed of 1mm / s to 500mm / s, defocus of +0mm to +2mm, laser pulse width of 100fs-20ps, frequency of 1KHz-70MHz, and laser wavelength of 300-1100nm.

[0107] In the present invention, copper circuits with different porosities, different aspect ratios and complex structures can be obtained by changing the laser parameters and the thickness of the copper electrode slurry coating, and copper circuits with different patterns can be obtained by arbitrarily changing the laser processing path, which has flexible controllability.

[0108] The method for preparing a solar cell provided by the present invention uses a laser to selectively pattern a copper electrode slurry coating with metal, and can directly obtain a copper circuit with a large aspect ratio and low resistivity, without causing damage to the laser unprocessed area, thereby improving the conversion efficiency of the solar cell. The method does not require multiple operations to increase the electrode thickness, nor does it require mask patterning and subsequent corrosion processes, and the process is simple. The method of multiple laser scanning can effectively increase the adhesion of the copper electrode, and can achieve the purpose of high efficiency and low cost.

[0109] In the method for preparing a solar cell provided by the present invention, there is no specific limitation on the laser processing system for the first laser scan and the Nth laser scan, and the laser processing system can be selected and assembled according to the specific type of the metal electrode to be prepared. The laser processing system used for the first laser scan and the Nth laser scan can be the same or different.

[0110] In one example, the first laser scan and the Nth laser scan use the same laser processing system.

[0111] In one example, the laser processing system includes a laser, an optical transmission system, a galvanometer system, and a three-dimensional moving platform. According to the needs of practical applications, the laser system may also include optical elements, a computer control system, a cooling system, and the like.

[0112] For example, Figure 4 As shown, the laser processing system includes a laser 10, an attenuation plate 11, an aperture 12, a glass slide 13, a beam expander 14, a reflector 15, a CCD image sensor 16, a scanning galvanometer 17, a field lens 18 and a three-dimensional moving platform 19. The laser can be a femtosecond laser, a picosecond laser or a continuous laser. After the laser outputs the laser, it passes through the attenuation plate, the aperture, the glass slide (which can be a 1 / 4 glass slide) and other optical elements, and then reaches the beam expander to expand the beam diameter, and then transmits it to the galvanometer through the reflector, and the galvanometer focuses the beam onto the processing sample surface of the three-dimensional moving platform for subsequent laser selective processing.

[0113] In the laser processing system, the beam expander is used to expand the beam diameter and reduce the focused spot size, and the reflector is used to change the direction of light path transmission. When the laser processing system is working, the laser emits a Gaussian beam, which is redirected by the reflector and transmitted to the galvanometer, which focuses the beam onto the surface of the copper electrode slurry coating. The laser prepares the Cu grid line by inducing reduction of the copper electrode slurry coating according to the designed path.

[0114] In one example, in (c), the water-based cleaning agent comprises a nonionic surfactant, an anionic surfactant, a defoaming agent and a phosphate detergent builder.

[0115] In one example, based on the total weight of the water-based cleaning agent, the content of the nonionic surfactant is 16-21% by weight, the content of the anionic surfactant is 1-3% by weight, the content of the defoaming agent is 1-3% by weight, and the content of the phosphate detergent builder is 1.5-6% by weight. The remaining components are water, and the sum of the components is the total weight of the water-based cleaning agent, which is calculated as 100%.

[0116] In one example, the nonionic surfactant as a main active agent may be selected from at least one of polyoxyethylene glycol lauryl alcohol ether (AEO-9), fatty alcohol polyoxyethylene ether (JFC-3) and alkylphenol polyoxyethylene ether (TX-10).

[0117] In one example, the compounded anionic surfactant is selected from at least one of sodium dodecyl diphenyl ether disulfonate (2A1), isooctyl alcohol polyoxyethylene ether phosphate and fatty acid hydroxyethane sulfonate.

[0118] In one example, the defoamer can be alcohols, amides, phosphates, polyethers, etc. For example, the defoamer is ethylenediamine PO-EO block copolymer (ED 3060), and other defoamers include tributyl phosphate, distearyl ethylenediamine, polyoxyethylene polyoxypropylene block copolymer, etc.

[0119] In one example, the phosphate detergent builder may be at least one of sodium tripolyphosphate, anhydrous sodium metaphosphate and sodium pyrophosphate.

[0120] In one example, based on the total weight of the water-based cleaning agent, the content of 2A1 is 1-3 weight %, the content of AEO-9 is 15-18 weight %, the content of JFC-3 is 1-3 weight %, the content of ED 3060 is 1-3 weight %, the content of sodium tripolyphosphate is 1-5 weight %, the content of anhydrous sodium metaphosphate is 0.5-1 weight %, and the remaining components are water.

[0121] In the present invention, the main components of the above-mentioned water-based cleaning agent are surfactants, detergent aids and buffer solutions, etc. The above-mentioned water-based cleaning agent is used to degrease and clean the silicon substrate of the heterojunction battery. During the cleaning process, the organic matter adsorbed on the surface of the silicon substrate can be removed by relying on the emulsification and saponification effects of the surfactant, thereby achieving the purpose of increasing the surface wettability and improving the surface tension, making the surface of the heterojunction battery easy to accept the coating, and improving the adhesion of the copper electrode slurry.

[0122] In one example, the solar cell is a silicon solar cell, specifically a monocrystalline silicon solar cell, a polycrystalline silicon thin film solar cell, and an amorphous silicon thin film solar cell. Preferably, it is a heterojunction solar cell, and it can also be other types of solar cells, as long as the transparent conductive film of the solar cell is provided with a periodic nanostructure array, and the metal electrode is prepared by the copper electrode slurry provided by the present invention, or is prepared by the method for preparing a solar cell of the present invention, it is within the protection scope of the present invention.

[0123] In one example, the basic structure of a heterojunction cell is referred to Figure 1 As shown, it mainly includes an n-type single crystal silicon wafer 4 (c-Si), an intrinsic amorphous silicon thin film layer 5 (ia-Si:H), an amorphous silicon film layer 3 (pa-Si:H), a transparent conductive film 2 (ITO) and a metal gate electrode 1.

[0124] In one embodiment, a method for preparing a heterojunction solar cell comprises the following steps:

[0125] (I) performing texturing and cleaning on an n-type single crystal silicon wafer, i.e. forming a texturing surface ("pyramid structure") on the surface of the silicon wafer;

[0126] (II) deposition of an amorphous silicon film, including deposition of an intrinsic amorphous silicon film and a doped amorphous silicon film, firstly depositing an intrinsic amorphous silicon film (ia-Si:H) and a p-type amorphous silicon film (pa-Si:H) on the front side of an n-type single crystal silicon wafer (c-Si), and then depositing an intrinsic amorphous silicon film (ia-Si:H) and an n-type amorphous silicon film (na-Si:H) on the back side of the silicon wafer to form a back surface field;

[0127] (III) Depositing transparent oxide conductive films on both sides of the cell.

[0128] Wherein, step (1) and step (II) prepare a silicon substrate.

[0129] In one example, in step (I), the texturing and cleaning can cause the incident light to be reflected and refracted multiple times on the surface of the single crystal silicon wafer, thereby extending the optical path, increasing the photogenerated carriers, and avoiding the recombination of carriers at the junction interface caused by defects and impurities introduced by uncleanliness.

[0130] In one example, in step (II), the amorphous silicon film is deposited by plasma enhanced chemical vapor deposition and hot wire chemical vapor deposition. Superior surface passivation ability is an important condition for obtaining higher cell efficiency. By utilizing the excellent passivation effect of amorphous silicon, the minority carrier lifetime of silicon wafers can be greatly improved.

[0131] In one example, in step (III), the deposition method of the transparent conductive film includes various physical vapor deposition (PVD), chemical vapor deposition (CVD), jet pyrolysis and sol-gel. Since amorphous silicon has poor conductivity, adding a transparent conductive film between the electrode and the amorphous silicon layer during the manufacturing process of heterojunction solar cells can effectively increase the collection of carriers, and can also play an anti-reflection role, and is a good window layer material.

[0132] In one example, the intrinsic amorphous silicon film (ia-Si:H) has a thickness of 0.1-10 nm.

[0133] In one example, the thickness of the p-type amorphous silicon film (pa-Si:H) is 0.1-10 nm.

[0134] In one example, the thickness of the n-type amorphous silicon film (na-Si:H) is 0.1-10 nm.

[0135] In one example, the thickness of the transparent conductive film (ITO) is 1-400 nm.

[0136] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0137] Unless otherwise specified, the materials and reagents used in the following examples can be obtained from commercial sources.

[0138] The present invention is described in detail below in conjunction with specific embodiments, which are used to understand but not to limit the present invention.

[0139] Preparation Example 1

[0140] A copper electrode slurry, the formula of which is as follows:

[0141] Metal composition: nano copper oxide (CuO NP), average particle size 30-50 nm, 10 parts by weight;

[0142] Dispersing reducing agent: polyvinyl pyrrolidone, 3.26 parts by weight;

[0143] Composite curing agent: bisphenol A epoxy resin (epoxy equivalent 182-192g / eq, viscosity 11000-14000cps), 0.5 parts by weight; PN-23J, 0.1 parts by weight;

[0144] Solvent: ethylene glycol, 6.76 parts by weight;

[0145] The copper electrode slurry is prepared by the following method:

[0146] (1) mixing the polyvinyl pyrrolidone and ethylene glycol in the formulated amounts in batches for multiple times (e.g., 4-5 times) and obtaining a mixed solution under the combined action of heating in a water bath at 45-65° C., magnetic stirring and ultrasonic vibration;

[0147] (2) Adding the formulated amount of nano copper oxide particles, epoxy resin and PN-23J to the mixed solution obtained in step (1) in batches for multiple times (for example, 4-5 times), and obtaining a copper electrode slurry under the combined action of heating in a water bath at 45-65° C., magnetic stirring and ultrasonic vibration.

[0148] Preparation Example 2

[0149] The preparation was carried out in accordance with Preparation Example 1, except that the copper electrode slurry had the following formula:

[0150] Metal composition: nano cuprous oxide (Cu2O NP), 10 parts by weight;

[0151] Dispersing reducing agent: polyvinyl pyrrolidone, 4 parts by weight;

[0152] Composite curing agent: polyurethane modified epoxy resin, 0.54 parts by weight; MY-25, 0.13 parts by weight;

[0153] Solvent: ethylene glycol, 10 parts by weight.

[0154] Preparation Example 3

[0155] The preparation was carried out in accordance with Preparation Example 1, except that the copper electrode slurry had the following formula:

[0156] Metal composition: CuO NP, 5 parts by weight, Cu2O NP, 5 parts by weight;

[0157] Dispersing reducing agent: polyvinyl pyrrolidone, 1.67 parts by weight;

[0158] Composite curing agent: acrylic modified epoxy resin, 0.43 parts by weight; PN-23J, 0.07 parts by weight;

[0159] Solvent: ethylene glycol, 6.25 parts by weight.

[0160] Preparation Example 4

[0161] This group of preparation examples is used to illustrate the effect of adjusting the components and proportions in the composite curing agent on the performance of the copper electrode slurry.

[0162] Preparation Example 4-1 was prepared by referring to Preparation Example 1, except that the composite curing agent was: epoxy resin, 0.83 parts by weight; PN-23J, 0.17 parts by weight;

[0163] Preparation Example 4-2 was prepared by referring to Preparation Example 1, except that the composite curing agent was: epoxy resin, 0.3 parts by weight; PN-23J, 0.3 parts by weight;

[0164] Preparation Example 4-3 was carried out with reference to Preparation Example 1, except that the composite curing agent was: epoxy resin, 0.5 parts by weight; PN-23J, 0.05 parts by weight; and MY-25, 0.05 parts by weight.

[0165] Example 1

[0166] A solar cell is obtained by the following preparation method:

[0167] (1) preparing a heterojunction battery substrate and depositing a transparent conductive film (ITO) on both sides of the substrate;

[0168] Specifically, the preparation of the heterojunction battery substrate includes the following steps: after texturing and cleaning the n-type monocrystalline silicon wafer, an intrinsic amorphous silicon film (ia-Si:H) and a p-type amorphous silicon film (pa-Si:H) are sequentially deposited on the front of the n-type monocrystalline silicon wafer (c-Si), and then an intrinsic amorphous silicon film (ia-Si:H) and an n-type amorphous silicon film (na-Si:H) are sequentially deposited on the back of the silicon wafer to form a back surface field; a transparent oxide conductive film is deposited on both sides of the battery. The texturing and cleaning, the deposition method of the intrinsic amorphous silicon film, and the deposition method of the transparent conductive film are as described above and will not be repeated here. The specific process parameters are carried out in accordance with the conventional operating methods in the field.

[0169] The thickness of the intrinsic amorphous silicon film (ia-Si:H) is 5 nm;

[0170] The thickness of the p-type amorphous silicon film (pa-Si:H) is 5 nm;

[0171] The thickness of the n-type amorphous silicon film (na-Si:H) is 5 nm;

[0172] The thickness of the transparent conductive film (ITO) is 100 nm.

[0173] (2) Using ultrafast laser to modify the surface of transparent conductive film to form a modified layer with periodic nanostructure; the specific laser processing parameters are: laser wavelength of 1060nm, laser pulse width of 190fs, laser flux of 0.66J / cm 2 , frequency is 5KHz, defocus distance is +1mm, speed is 2mm / s;

[0174] Laser polarization uses laser linear polarization, and the polarization direction is the same as the laser scanning direction;

[0175] The resulting periodic nanostructures are Figure 6 As shown in (a) and 7(a), the stripe length is 100nm-1000nm, the stripe depth is 10nm-50nm, and the average stripe width is 100-300nm.

[0176] (3) Using a water-based cleaning agent to clean the ITO surface of the heterojunction battery to remove impurities and grease on the ITO surface; wherein the total weight of the water-based cleaning agent is used as a reference, AEO-9 16 weight%, JFC-3 2 weight%, 2A1 content is 2 weight%, ED 3060 2 weight%, sodium tripolyphosphate 4 weight%, anhydrous sodium metaphosphate 0.8 weight%, and the remaining components are water.

[0177] (4) Using a four-sided coater, the copper electrode slurry provided in Preparation Example 1 is applied to the surface of the heterojunction battery ITO cleaned in step (2), and dried in a drying oven at 50° C.-70° C. for 20-40 min to obtain a dry copper electrode slurry coating with a coating thickness of 7 μm-15 μm.

[0178] (5) Laser scanning is used to selectively metal pattern the dried copper electrode slurry coating according to the designed path; the processing parameters of the laser scanning are: laser pulse energy of 79nJ, laser scanning speed of 6mm / s, defocus of +0.6mm, number of laser scans of 1, laser pulse width of 9ps, repetition frequency of 2MHz, and laser wavelength of 532nm.

[0179] (6) Rinse with deionized water to remove the remaining copper electrode slurry coating in the unprocessed area to obtain a heterojunction solar cell copper electrode.

[0180] The laser processing system for laser scanning in step (5) is as follows: Figure 2 The schematic diagram of the laser processing system includes a picosecond laser, an attenuation plate, an aperture, a quarter glass, a 4x beam expander, a reflector, a CCD image sensor, a scanning galvanometer, a field mirror, and a three-dimensional moving platform. When the laser processing system is working, the picosecond laser emits a Gaussian beam, which is redirected by the reflector and transmitted to the galvanometer, which focuses the beam onto the surface of the copper electrode slurry coating. The laser prepares the Cu gate line by inducing reduction of the copper electrode slurry coating according to the designed path.

[0181] The three-dimensional morphology of the Cu gate line obtained in this embodiment is shown in the schematic diagram of the structure. Figure 8 As shown, a copper electrode with a uniform and fine surface and a line width of about 40 μm can be directly prepared by laser selective metal patterning. It should be noted that the copper electrode line width prepared by this laser processing system can be as small as 16 μm, but the improvement of resolution will lead to a decrease in resistivity, and the minimum width of the prepared copper electrode is related to the laser spot diameter. Changing the laser equipment can obtain a lower line width.

[0182] The surface of the copper electrode was observed using a field emission scanning electron microscope, and the elemental composition of the copper circuit was analyzed using EDS. It was found that the copper circuit structure obtained in this example was dense and a lower porosity could be obtained. By analyzing the elemental composition through X-ray energy spectrum, the Cu:O ratio of the copper electrode obtained in this example increased from 1.8:1 before processing (copper electrode slurry) to 23.2:1, and the Cu / O content was greatly improved, reflecting that the Cu element was fully reduced at this time.

[0183] Example 2

[0184] The process was carried out in accordance with Example 1, except that radial polarization was used for laser polarization, and the specific processing parameters were: laser energy flux density was 0.3 J / cm 2 , frequency is 100KHz, defocusing amount is +1mm, speed is 2mm / s; the top view of the obtained surface nanostructure is shown in Figure 6 (b) shows the three-dimensional image. Figure 7 As shown in (b), the surface structure shows a concentric ring distribution.

[0185] Example 3

[0186] The process is carried out in accordance with Example 1, except that the laser polarization adopts azimuthally polarized light, and the specific processing parameters are: the laser energy flux density is 0.6 J / cm 2 , frequency 50KHz, defocusing amount +1mm, speed 10mm / s; the top view of the obtained surface nanostructure is shown in Figure 6 (c) shows the three-dimensional image. Figure 7As shown in (c), the surface structure shows a radial stripe distribution.

[0187] Example 4

[0188] The process was carried out with reference to Example 1, except that the processing parameters of the laser scanning in step (5) were: laser pulse energy of 100 nJ, laser scanning speed of 5 mm / s, defocusing amount of +0.6 mm, number of laser scanning times of 1, laser pulse width of 9 ps, repetition frequency of 2 MHz, and laser wavelength of 532 nm. The prepared Cu circuit was compared with Example 1, and a copper electrode with good surface morphology, low porosity, and dense structure was obtained.

[0189] Example 5

[0190] The process was carried out with reference to Example 1, except that the processing parameters of the laser scanning in step (5) were: laser pulse energy of 100 nJ, laser scanning speed of 8 mm / s, defocus of +0.6 mm, number of laser scanning times of 1, laser pulse width of 9 ps, repetition frequency of 2 MHz, and laser wavelength of 532 nm. The prepared Cu circuit was compared with Example 1. Due to the increase in scanning speed and the reduction reaction time, the copper electrode obtained in this example had poor continuity, but the overall morphology was complete.

[0191] Example 6

[0192] The process was carried out with reference to Example 1, except that the processing parameters of the laser scanning in step (5) were: laser pulse energy of 79 nJ, laser scanning speed of 6 mm / s, defocus of +0.8 mm, number of laser scans of 1, laser pulse width of 9 ps, repetition frequency of 2 MHz, and laser wavelength of 532 nm. The prepared Cu circuit was compared with that in Example 1. Due to the increase in defocus and the decrease in laser energy density, the Cu circuit morphology obtained in this example had a small number of defects, but the overall morphology was complete.

[0193] Example 7

[0194] Refer to Example 1, except that after the laser scanning in step (5) is completed, a second laser scanning is performed, and the processing parameters of the second laser scanning are: laser pulse energy is 500nJ, laser scanning speed is 6mm / s, defocus is +0.6mm, number of laser scans is 1, laser pulse width is 9ps, repetition frequency is 2MHz, and laser wavelength is 532nm.

[0195] Example 8

[0196] The process is carried out in accordance with Example 1, except that after the laser scanning in step (5) is completed, 50 laser scans are further performed, and the processing parameters of the 50 laser scans are: laser pulse energy of 35 nJ, laser scanning speed of 6 mm / s, defocus of +0.6 mm, number of laser scans of 1, laser pulse width of 9 ps, repetition frequency of 2 MHz, and laser wavelength of 532 nm.

[0197] Examples 9-13

[0198] Examples 9-13 were carried out with reference to Example 1, except that in step (4) of Examples 9-13, the copper electrode slurries prepared by Preparation Example 2, Preparation Example 3, Preparation Example 4-1, Preparation Example 4-2 and Preparation Example 4-3 were used respectively.

[0199] Comparative Example 1

[0200] The process was carried out in accordance with Example 1, except that the processing parameters of the laser scanning in step (5) were: laser pulse energy of 35 nJ, laser scanning speed of 6 mm / s, defocus of +0.6 mm, number of laser scans of 1, laser pulse width of 9 ps, repetition frequency of 2 MHz, and laser wavelength of 532 nm. The lower energy was insufficient to completely reduce CuO to Cu, and the resulting copper circuit had poor morphology.

[0201] Comparative Example 2

[0202] The process was carried out with reference to Example 1, except that the processing parameters of the laser scanning in step (5) were: laser pulse energy of 100 nJ, laser scanning speed of 2 mm / s, defocus of +0.6 mm, laser scanning times of 1, laser pulse width of 9 ps, repetition frequency of 2 MHz, and laser wavelength of 532 nm. The prepared Cu circuit was compared with that in Example 1. The copper circuit obtained in this example was severely oxidized due to the slow scanning speed.

[0203] Comparative Example 3

[0204] The process was carried out in accordance with Example 1, except that the processing parameters of the laser scanning in step (5) were: laser pulse energy of 79 nJ, laser scanning speed of 6 mm / s, defocus of +0.2 mm, laser scanning number of 1, laser pulse width of 9 ps, repetition frequency of 2 MHz, and laser wavelength of 532 nm. Compared with Example 1, the prepared Cu circuit was found to have a smaller spot diameter and an excessively large laser energy density, resulting in ablation of the CuO nanocoating and failure to restore a better copper circuit.

[0205] Comparative Example 4

[0206] The same process is carried out as in Example 1, except that step (2) is not performed.

[0207] Comparative Example 5

[0208] The process is carried out in accordance with Example 1, except that in step (3), ethanol is used instead of the water-based cleaning agent.

[0209] Test Case

[0210] (1) The above-mentioned Examples 1-13 and Comparative Examples 1-5 were tested to obtain the binding strength of the metal electrodes of the solar cell, and the hundred-grid method was used for testing. The test results were divided into six levels: 0B, 1B, 2B, 3B, 4B, and 5B. 0B-5B represent a greater binding strength, that is, 5B has the strongest binding strength. The results are recorded in Table 1.

[0211] (2) The resistivity of the solar cells obtained by testing the above-mentioned Examples 1-13 and Comparative Examples 1-5 was measured by a four-probe method. The results are recorded in Table 1.

[0212] Table 1

[0213]

[0214]

[0215] It can be seen from the experimental data in Table 1 that changing the total content of the composite curing agent will change the resistivity and adhesion. A high content of the composite curing agent will lead to an increase in the resistivity (see Example 11), and a low content of the composite curing agent will affect the adhesion. The internal ratio of the composite curing agent affects the curing effect, i.e., the adhesion, and has little effect on the resistivity; the periodic nanostructure mainly affects the adhesion, and has little effect on the resistivity. With multiple processing, the resistivity can be reduced and the adhesion can be improved.

[0216] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A solar cell, characterized in that: The invention comprises a silicon substrate and a transparent conductive film, wherein a periodic nanostructure array is arranged on the transparent conductive film.

2. The solar cell according to claim 1, wherein: The transparent conductive film is processed by ultrafast laser, and the conditions of the ultrafast laser processing include laser polarization; Preferably, the laser polarization includes linear polarization and / or circular polarization.

3. The solar cell according to claim 2, wherein: The processing parameters of the ultrafast laser include: laser wavelength of 300nm-1060nm, laser pulse width of 100fs-20ps, laser energy flux density of 0.1J / cm 2 -10J / cm 2 , frequency is 1KHz-1MHz, laser scanning speed is 0.1mm / s~100mm / s, and defocus is +0mm~+2mm.

4. The solar cell according to claim 1, wherein: It also includes a metal electrode disposed on the surface of the transparent conductive film, wherein the metal electrode is prepared by using copper electrode slurry and laser technology; The copper electrode slurry comprises a metal composition, a dispersing reducing agent, a composite curing agent and optionally a solvent; the metal composition comprises at least copper powder, and optionally gold powder and / or silver powder; the composite curing agent comprises a thermosetting resin and a latent curing agent.

5. The solar cell according to claim 4, wherein: The thermosetting resin is selected from at least one of epoxy resin, polyurethane-modified epoxy resin, acrylic-modified epoxy resin, polyamide resin, polyurethane resin and acrylic resin; And / or, the latent curing agent includes a latent amine curing agent and / or an imidazole curing agent; And / or, the reducing dispersant is selected from at least one of polyvinyl pyrrolidone and its derivatives; And / or, the solvent is selected from C1-C6 low-carbon alcohols; And / or, the metal composition includes nano copper oxide and / or nano cuprous oxide.

6. The solar cell according to claim 4 or 5, wherein: The mass ratio of the metal composition to the composite curing agent is (7-30):1; And / or, the mass ratio of the thermosetting resin to the latent curing agent is (4-6):1; And / or, the mass ratio of the metal composition to the composite curing agent is (15-20): 1 And / or, the mass ratio of the metal composition to the dispersing reducing agent is (2-9):1, preferably (2.5-6):

1.

7. A method for preparing a solar cell according to any one of claims 1 to 6, characterized in that: This involves using ultrafast lasers to process transparent conductive films.

8. The method according to claim 7, characterized in that The following steps are involved: (1) Using ultrafast laser to process the surface of transparent conductive film; (2) placing a copper electrode slurry on the surface of the transparent conductive film treated in step (1); (3) Performing a first laser scan on the copper electrode slurry coating on the surface of the transparent conductive film in step (2).

9. The method according to claim 8, characterized in that The method further comprises step (4), performing an Nth laser scan on the copper electrode slurry of step (2), where N≧2; Preferably, the laser energy of the Nth laser scan is higher than the laser energy of the first laser scan.

10. The method according to claim 8, wherein: The step of pre-cleaning the transparent conductive film is also included, wherein the transparent conductive film is cleaned with a water-based cleaning agent before the copper electrode slurry is set; Preferably, based on the total weight of the water-based detergent, the content of nonionic surfactant is 16-21 weight %, the content of anionic surfactant is 1-3 weight %, the content of defoaming agent is 1-3 weight %, and the content of phosphate detergent aid is 1.5-6 weight %.

Citation Information

Patent Citations

  • Heterojunction solar cell with plated seed layer prepared by in-situ reduction, and preparation method thereof

    CN110137278A

  • Electrode slurry for heterojunction solar cell and preparation method thereof

    CN111048233A

  • Method for preparing flexible copper circuit by laser-induced reduction sintering of copper oxide ink

    CN111970842A

  • Mask-free preparation method of copper electrode of heterojunction solar cell

    CN113066897A

Cited By

  • Crystalline silicon photovoltaic cell and preparation method thereof

    CN122602691A